Women Peacekeepers in United Nations peace operations: Critical to mitigate gender-based violence in a mission area - Sharma,K.K. (U.S.I. Journal)
United Nations Peace Operations (UNPOs) have been used as a of the successful tools in a protracted conflict to enable a country to transition into a peaceful existence and long-term development. Despite scepticism, this endeavour has met with many successes over the past 75 years. Unfortunately, the world continues to witness ever-increasing conflicts, replete with different forms of gender-based violence, often targeting women and children. In such situations, the United Nations (UN) and most member states acknowledge that women-peacekeepers can play a crucial role. UN Security Council (UNSC) Resolution 1325 (2000) also recognised the role of women peacekeepers as an enabling factor. With the UNSC Resolution 1820 (2008), UNPOs came under increased pressure to prevent conflict-related sexual violence, which is largely attributed to local security actors. In this article, a systematic review of the academic and other literature was used to ascertain the efficacy and effectiveness of women peacekeepers in the mitigation of gender based violence. the role of women peacekeepers was considered a crucial independent variable for the protection outcome. the article brings out that the women peacekeepers play a critical role in peacekeeping missions, contributing their unique perspectives and skills that enhance operational effectives and skills that enhance operational effectiveness. the UN has been setting targets for the number of women peacekeepers and most contributing countries are obliging. However, they also face significant challenges in their recruitment, training, deployment and participation. it has also been highlighted that the UN field operations are still heavily biased towards male-dominated and aggressive infantry-dominant deployments. the result are also dependent on the sufficient presence of women peacekeepers in the sector. The article addresses a significant gap in academic discourse, as the influence of women in peacekeeping is infrequently discussed and scholarly opinions on their actual impact differ. It points towards a limited yet positive influence of women peacekeepers on gender-based violence and overall mission effectiveness.Reproduced
Keywords: United Nations Peace Operations, UNPOs, United Nations (UN), Women-peacekeepers, UN Security Council(UNSC)